Development and validation of a web-based patient decision aid for immunotherapy for patients with metastatic melanoma: study protocol for a multicenter randomized trial - Grabbe, Pia; Gschwendtner, Kathrin M.; Maatouk, Imad; Strobel, Sophia; Salzmann, Martin; Bossert, Julia; Eich, Wolfgang; Wild, Beate; Meier, Friedegund; Hassel, Jessica C.; Bieber, Christiane (Trials, 2021)
Patients with metastatic melanoma and their physicians are confronted with a complex decision regarding first-line therapy. Risks and benefits vary considerably between various treatment options. With this in mind, we aim to develop and evaluate a patient decision aid (PtDA) to inform patients about the risks and benefits of treatment options, namely, immunotherapy as monotherapy, immunotherapy as combination therapy, and treatment with BRAF/MEK inhibitors. We aim to test whether the use of this PtDA before medical consultation will increase patients’ knowledge of treatment options and thus promote shared decision-making (SDM) and patient decision satisfaction.